Introduction to the Importance of Waste Management for Elementary School Students in Sumberejo Village, Madiun - Lintang, Alfonsius; Andiyani, Razita Sabrina Putri; Tiviani, Zaira; Indraputri, Amara Jasmine; Aisyavarya, Fisca Dwanda Caesara; Yunas, Novy Setia (Sahwahita: Community Engagement Journal, 2024)
In 2022, based on data from the National Waste Management Information System (SIPSN) and the Ministry of Environment and Forestry (KLHK), Indonesia produced around 19.45 million tons of waste. The increase in waste continues with the increasing population and community consumption. The waste management program at the elementary school level aims to increase student awareness of waste reduction, environmental conservation, and participation in recycling practices. Socialization is carried out through material presentations, recycling practices, and interactive Q&A, with a focus on the role of individuals in protecting the environment. This program took place at SD Desa Sumberejo, Madiun District, Madiun Regency, and involved students in organic and inorganic waste sorting activities. The results of the activities showed an increase in students' understanding of the concept of recycling and their motivation to take real action, such as managing waste independently. The high enthusiasm from students and the positive response from the school showed the success of the socialization. However, the effectiveness of long-term behavioral change was measured through post-program surveys and follow-up observations that showed an increase in waste sorting in the school environment as an indicator of the program's sustainability.